The role of the school guidance counselor in reducing academic failure - GUENDOUZ, MAHMOUD (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The study aimed to identify the role of the school guidance counselor in reducing academic failure among secondary school students from their point of view. The study relied on the descriptive analytical approach; and through the questionnaire prepared by the researcher and designed to measure the student's attitudes towards role. The study concluded the following: - The school guidance counselor contributes to helping raise the level of academic achievement. - The school guidance counselor advisor contributes to modifying the wrong behaviors that lead to academic failure. -The school guidance counselor contributes to facing psychological problems that lead to academic failure. *- المؤلف المرسل The role of the school guidance consultant is important in reducing the academic failure from the point of view of secondary school students and this shows the degree of awareness of the student of the importance of the aspects mentioned, fighting the failure of the school is not only related to the extent of the diligence of the learner and his keenness to study, but also the methods of studying and his awareness of strategies that suit him in his learning and awareness of his abilities and needs is also important to achieve success, in addition to behavioral discipline within and outside the educational institution and the selection of good companionship and to stay away from all behaviors that may hinder the process of studying and finally consciousness The importance of psychosocial compatibility, which is the first incentive and motivation to achieve comfortable and successful learning.